The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11858-020-01139-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing prospective mathematics teachers’ diagnostic processes in a simulated environment

Abstract: Diagnostic competences are an essential facet of teacher competence. Many studies have investigated the quality of teachers' judgments of students' competences. However, little is known about the processes that lead to these judgments and about the ways to promote these processes in the early phase of teacher training. The aim of the research project on which we report in this paper was to develop a simulated computer-based environment that allows assessing and promoting the diagnostic processes of prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 27 publications
0
32
0
3
Order By: Relevance
“…Für eine Analyse von komplexen Lernendenmerkmalen unter einer fachdidaktischen Perspektive erweist sich diese Art von Videos als eher ungeeignet (von Aufschnaiter und Rogge 2010; Wildgans-Lang et al 2020). Es empfiehlt sich daher, die Komplexität der gezeigten Situationen einerseits zu reduzieren und andererseits auf einzelne Inhalte zu fokussieren (Olson et al 2016;Wildgans-Lang et al 2020). Dies kann bspw.…”
Section: Der Förderliche Einsatz Von Videovignetten Im Rahmen Des Falunclassified
See 2 more Smart Citations
“…Für eine Analyse von komplexen Lernendenmerkmalen unter einer fachdidaktischen Perspektive erweist sich diese Art von Videos als eher ungeeignet (von Aufschnaiter und Rogge 2010; Wildgans-Lang et al 2020). Es empfiehlt sich daher, die Komplexität der gezeigten Situationen einerseits zu reduzieren und andererseits auf einzelne Inhalte zu fokussieren (Olson et al 2016;Wildgans-Lang et al 2020). Dies kann bspw.…”
Section: Der Förderliche Einsatz Von Videovignetten Im Rahmen Des Falunclassified
“…Diagnostische Prozesse im Unterrichtsgeschehen sind hochgradig komplex (Heitzmann et al 2019). Zu Zwecken der Förderung diagnostischer Fähigkeiten ist der Einsatz von unterrichtsrealistischen Lernumgebungen daher weniger zielführend (Wildgans-Lang et al 2020). Vielmehr ist eine Reduktion dieser Komplexität bei gleichzeitiger Fokussierung auf einzelne Inhalte bzw.…”
Section: Gruppenzusammensetzung Und Einfluss Des Designsunclassified
See 1 more Smart Citation
“…The first theme, addressed in various contributions, involves the construction and validation of instruments aimed at assessing teachers' situated professional knowledge, ranging from scenario-based questionnaires (Gasteiger et al 2020) to video-based assessments (Blömeke et al 2020;Kersting et al 2020;Krauss et al 2020) and online simulation environments (Charalambous 2020;Wildgans-Lang et al 2020). Moderate correlations have been observed between teachers' performances on these measures of situated knowledge and paper-and-pencil tests that are developed following a cognitive perspective on teacher knowledge (Charalambous 2020;Gasteiger et al 2020;Krauss et al 2020).…”
Section: Major Themes Of Our Review and Issues For Future Researchmentioning
confidence: 99%
“…It has also been revealed that there exists a link between Subject-Matter Knowledge (CCK, SCK) and Pedagogical Content Knowledge (KCS). KCS improves instructional quality of mathematics teachers(Ünver, Özgür, and Güzel, 2020;Wildgans-Lang et al, 2020; Yang et al, 2020) Thus, mathematics teacher education providers in Zambian colleges of education and universities are urged to design educational courses that are aimed at addressing secondary school mathematics. The said courses should have special focus on the concept of a function because it is a central topic in secondary school mathematics and in advanced university mathematics.…”
mentioning
confidence: 99%